Contraceptive Use and Associated Factors Among HIV-Positive Women on Antiretroviral Therapy in Western Nepal: A Cross-Sectional Study: Contraceptive use among HIV positive women - Ruchal, Rajendra; Shrestha, Niranjan (NPRC Journal of Multidisciplinary Research, 2026)
Background: Mother with human immunodeficiency virus positive must plan their pregnancies carefully in order to avoid unwanted pregnancy and prevent vertical transmission to their unborn children. The use of contemporary contraceptive techniques is greatly increased when contraceptive services are integrated into antiretroviral therapy service. We assessed the utilization of modern contraceptives and related factors among HIV positive women attending the antiretroviral therapy clinic at Lumbini provincial hospital, Butwal. Objective: To evaluate the prevalence and risk factors for using contraception among HIV-positive women using antiretroviral medicine. Methodology: A cross-sectional study was conducted among 422 HIV-positive women at the ART centre of Lumbini Provincial Hospital. The sample size was calculated using a single population proportion formula (95% CI, 5% margin of error, 50% prevalence), and data were collected via a pretested questionnaire and analysed in SPSS. Data were collected using a structured pretested questionnaire and analysed in SPSS. Multivariable logistic regression was used to identify factors associated with contraceptive use, reporting adjusted and unadjusted odds ratios with 95% confidence intervals. Results: Contraceptive use among HIV-positive women was 39.6%, condoms were the most commonly used method (38,3%) and only 26.5% received family planning counselling. Age (aOR = 0.53, 95% CI: 0.31–0.84, p = 0.008), marital status (aOR = 2.52, 95% CI: 1.53–4.65, p < 0.001), having children (aOR = 0.17, 95% CI: 0.05–0.49, p = 0.002), and monthly income (aOR = 2.4, 95% CI: 1.37–3.99, p = 0.002) were significant independent predictors of contraceptive use. Conclusion: Low contraceptive use and limited counselling among HIV-positive women indicate gaps in ART-based reproductive health services. Integrating family planning into ART care and addressing socio-demographic barriers through targeted interventions and multi-sectorial collaboration is essential to improve uptake and support informed reproductive choices.